Exercise training versus diet-induced weight-loss on metabolic risk factors and inflammatory markers in obese subjects: a 12-week randomized intervention study - Christiansen, Tore; Paulsen, Søren K.; Bruun, Jens M.; Pedersen, Steen B.; Richelsen, Bjørn (American journal of physiology: endocrinology and metabolism, 2010)
The purpose of this study was to investigate the effect of exercise training and diet-induced weight loss alone or in combination on inflammatory markers in circulation, in adipose tissue (AT) and in skeletal muscle (SM) in obese subjects. Seventy-nine obese subjects were randomized into a 12-wk intervention: 1) exercise only (EXO), 2) diet-induced weight loss using a very low energy diet (DIO), and 3) exercise and diet-induced weight-loss combined (DEX). Blood samples (metabolic and inflammatory markers) and AT and SM biopsies (mRNA expression) were collected at baseline and after 12 wk. In the EXO group the weight loss was 3.5 kg and in the DIO and DEX groups it was 12 kg in both. V̇o 2max was increased by 14–18% in the EXO and DEX groups with no changes in the DIO group. In the DIO and DEX groups, circulating levels of MCP-1, MIP-1α, IL-15, and IL-18 were decreased, and adiponectin was increased ( P < 0.05 for all). In the EXO group, MCP-1 was decreased with 10% ( P = 0.06). By combining the weight loss in all three groups, we found a correlation between the degree of weight loss and improvement in several of the inflammatory markers ( P < 0.05). In AT biopsies, subjects in the DIO and DEX groups achieved a general beneficial but nonsignificant effect on the gene expression of inflammatory markers. In the EXO group, no changes in AT adipokine mRNA were found except for an increment of adiponectin ( P < 0.05). In SM, the only observed change was that the gene expression of IL-6 was increased in all three groups ( P < 0.05). In conclusion, rather large weight losses (>5–7%) were found to have beneficial effects on circulating inflammatory markers in these obese subjects. Aerobic exercise for 12 wk, which increased V̇o 2max , was found to have no effects on circulating inflammatory markers in these obese patients. It is suggested that more intensive exercise may be necessary to affect systemic inflammation.